Power, Social Media, Social Movements:A Bourdieuian Path to Discovering the Power of Social Movements Within the Space of Social Media - Geukjian, Katrina (Université d'Ottawa | University of Ottawa, 2013)
Communication technologies in the 21st century have changed how social movements have been able to develop, organize and mobilize. Social media has become a space where these social groups can acquire power, enabling them to increase the social status of an ideology. This paper will show how and when social movements can gain power within social media by using Bourdieu’s concepts of power and practice. The development of communication technology, the socialization of social media and the transference of social and cultural identity into the space will show how Bourdieu’s concept of habitus shapes our approach to social media and allows social movements to form within it. Social movements can accrue power through Bourdieu’s concept of social and symbolic capital. They can acquire social capital by using collective ideology to attract followers. Social movements can also use misrecognition, symbolic language and their ability to distance themselves from a negatively perceived social norm to accrue symbolic capital. The accrued capital allows the social movement to gain recognition and legitimation, which in turn increases their social standing within a field. Bourdieu’s concept of field, in this case represented by the socially structured space within social media, is made possible by the inherent characteristics of the space; its capacity to reproduce social structures and function as a space where social movements can strive to increase their social standing and the status of an ideology through acquired capital. These elements will demonstrate how and when social movements can acquire power within the space of social media. Furthermore, this paper will go beyond Bourdieu’s definitions of habitus, capital and field by exploring the limits of each concept in relation to social media, the transference of identity from the ‘real’ embodied realm to the ‘virtual’ disembodied realm, and a social movement’s ability to use accrued power to mobilize action outside of the field of social media.